Proceedings of the 4th International Symposium on Information, Computer, and Communications Security 2009
DOI: 10.1145/1533057.1533067
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight self-protecting JavaScript

Abstract: This paper introduces a method to control JavaScript execution. The aim is to prevent or modify inappropriate behaviour caused by e.g. malicious injected scripts or poorly designed third-party code. The approach is based on modifying the code so as to make it self-protecting: the protection mechanism (security policy) is embedded into the code itself and intercepts security relevant API calls. The challenges come from the nature of the JavaScript language: any variables in the scope of the program can be redef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
111
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(112 citation statements)
references
References 23 publications
0
111
1
Order By: Relevance
“…This is because JavaScript performs an implicit type conversion. This attack was already addressed in [25] where it is credited to Maffeis (see also [19]). It is also the basis of a recently described attack on ADsafe [18].…”
Section: Self Protecting Javascriptmentioning
confidence: 98%
See 3 more Smart Citations
“…This is because JavaScript performs an implicit type conversion. This attack was already addressed in [25] where it is credited to Maffeis (see also [19]). It is also the basis of a recently described attack on ADsafe [18].…”
Section: Self Protecting Javascriptmentioning
confidence: 98%
“…Within this area one can roughly divide the approaches into those which transform the whole program (thus requiring the program to be parsed) and those which perform wrapping without having to modify the code. Phung et al [25] refer to these styles as invasive vs lightweight, respectively. The former approach is taken by the BrowserShield tool [28] which performs a deep wrapping of code, requiring run-time parsing and transformation of the code.…”
Section: The Wrapper Landscapementioning
confidence: 99%
See 2 more Smart Citations
“…A short workshop paper [27] also gives an architecture for server-side code analysis and instrumentation, without exploring details or specific methods for constraining JavaScript. Additional related work on rewriting based methods for controlling the execution of JavaScript include [12]. Foundational studies of limited subsets of JavaScript and dynamic languages in general are reported in [2], [25], [28], [11], [21], [1], [26]; see [16].…”
Section: Introductionmentioning
confidence: 99%